Väitöskirjoja lapsen fonologiasta - Iivonen, Antti (Virittäjä, 2006)
Kirja-arvio Kunnari, Sari: Characteristics of early lexical and phonological development in children acquiring Finnish;Turunen, Pirjo: Production of word structures: A constraint-based study of 2;6 year old Finnish children at-risk for dyslexia and their controls